Religious conflict, sharia question and Nigerian unity (2009)
One of the noticeable problems in Nigeria’s political history is religious conflict. Religious conflict has threatened the unity of Nigeria, because of the inherent politics played along with it. However, this problem was an age long phenomenon, as old as the emergence of modem Nigeria, with the advent of Christianity and Islam; and the attendant modes of worship and hatred for each other. The complexity of religion has adversely affected inter-group relations in Nigeria. Indeed the use of religion to gain political power is noticed, and has become a do or die affair, especially for attaining other benefits (social and economic) through the state. Today, the Sharia issue has become controversial not essentially because of its religious essence but for its political expediency. This paper explores the effects of religious conflict .and the Sharia issue on Nigerian governmental policies, and examines its impact on socio-economic development. The paper argues that in a pluralistic society like Nigeria, this conflict is inevitable due to the ethno-cultural diversities and the universal claims of the two religions, but the responsibility of government is largely based on how best to manage and resolve these conflicting world views within the polity. The paper concludes that no matter the contradiction of secularism in our constitution, it is still the only alternative measure in resolving religious conflict for the unity of Nigeria within the context of a true federalism